A new method for self-organized dynamic delay loop associated pipeline with reconfigurable computing system - Nandigam Suresh Kumar; Dasari Vijaya Lakshmi; Bejjanki Pooja Sree Prasanna; Dodda Venkata Rama Koti Reddy (Institute of Advanced Engineering and Science, 2022)
The minimization of propagation delay between pipeline stages is very important in wave propagation through pipeline-stages. The propagation delay can be minimized by minimizing the number of stages in a pipeline. In the proposed design a dynamic stage control is imparted in the pipeline. The propagation delay can be optimized in any type of pipeline by controlling number of stages dynamically. The pipeline interpretation helps a lot to overcome the flaws due to not ready sequence (NRS) and synchronization problems. It is observed that, in the pipeline design the basic and actively involved pipeline techniques are concerned with different challenges like clock, throughput, cell area, and sizes. As the data throughput increases the number of stages in pipeline also needs to be increased to meet the desired goal. In the case of unpredictable data speed, the definite number of pipeline stages creates severe problems. In this work a dynamic pipeline is integrated where the number of stages is dynamically changing depending up on data speed. In dynamic pipeline technique the circuit cell area of reconfigurable computing system (RCS) will be reduced dynamically at low-speed data transmission. In the high-speed data communication, the data speed is managed and controlled by dynamic delay loops.